Durability to Natural Weathering of Methylene Diphenyl Diisocyanate-Bonded Bamboo Oriented Strand Board - Lestari, Dini; Suwanda, Astri Aulia; Murda, Rio Ardiansyah; Maulana, Muhammad Iqbal; Augustina, Sarah; Rianjanu, Aditya; Taher, Tarmizi; Hidayat, Wahyu; Maulana, Sena; Lubis, Muhammad Adly Rahandi (Jurnal Sylva Lestari, 2024)
This study aimed to examine the qualities of bamboo-oriented strand board (BOSB) made from Dendrocalamus asper bamboo strands, both with and without steam treatment. Furthermore, the effect of exposure length to natural weathering on the physical and mechanical characteristics of BOSB was examined. The steam treatment lasted one hour at 126°C and a pressure of 0.14 MPa. Methylene diphenyl diisocyanate (MDI) and paraffin were utilized as adhesives and additives, with concentrations of 5% and 1%, respectively, based on oven-dried weight. The BOSB was exposed to natural weathering in different exposure durations (0, 1, and 3 months) in Bukit Bogor Raya Pajajaran, West Java, Indonesia. Subsequently, the BOSB was tested for its physical and mechanical properties and retention value. The result showed that steam treatment improved the dimensional stability and mechanical properties of BOSB bonded with MDI adhesive more than untreated BOSB. However, steam treatment has a better protection level against natural degradation than untreated samples. These confirm that BOSB with steam treatment is a durable and sustainable construction material. Keywords: bamboo, methylene diphenyl diisocyanate, natural weathering, oriented strand board, steam treatment